Splitting Tensile Strength of Soft Clay–Coconut Coir Fiber Mixtures Soaked in NaOH at Various Concentrations - Pandu Perdana Putra; Anita Widianti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Soil strength plays a crucial role in construction and geotechnical engineering. Weak soils, such as soft clay, often exhibit low bearing capacity, necessitating ground improvement techniques to ensure structural stability. One promising method for soil reinforcement involves the use of natural fibers, particularly coconut coir, which can be chemically treated to enhance its bonding with soil particles. This study investigates the effect of sodium hydroxide (NaOH) treatment on coconut coir fibers and its influence on the splitting tensile strength of a soil–fiber mixture. Coconut coir fibers, measuring 3–5 cm in length and incorporated at a content of 0.6%, were soaked in NaOH solutions of varying concentrations (0%, 5%, 10%, 15%, and 20%) for three hours prior to mixing. The treatment aimed to roughen the fiber surface and improve mechanical interlocking with the soil matrix. Splitting tensile strength tests were conducted following the SNI-2491 standard, with three specimens prepared for each NaOH concentration. The results indicate that NaOH treatment did not significantly enhance the splitting tensile strength of the soil–fiber mixture. The highest average splitting tensile strength, 33.48 kPa, was observed in samples reinforced with untreated fibers (0% NaOH). These findings suggest that, for coconut coir fibers of this size and content, chemical treatment with NaOH may not be necessary for improving soil tensile performance.